THE ROLE OF FEEDBACK LITERACY IN IMPROVING ASSESSMENT OUTCOMES IN EFL CONTEXTS - Samiyeva Nazokat Olim qizi; Khonsaidova Maktuba Makhamadalievna (TADQIQOTLAR, 2026)
ABSTRACT Feedback literacy plays a crucial role in improving assessment outcomes in EFL contexts by enabling learners to understand, interpret, and effectively use feedback for learning improvement. In many EFL settings, students often fail to engage meaningfully with feedback, limiting its impact on language development. This paper highlights the importance of developing feedback-literate learners who can actively reflect on and act upon feedback to enhance their performance. It argues that integrating feedback literacy into classroom practice promotes learner autonomy, deeper engagement with assessment, and improved language proficiency.